Ethnobotanical Study on Plants Used by Local People in Dusun Beleq, Gumantar Village, North Lombok Regency - Jannaturrayyan, Sawmi; Sukenti, Kurniasih; Rohyani, Immy Suci; Dao, Sukiman (Biosaintifika: Journal of Biology & Biology Education, 2020)
The traditional use of plants by people in Indonesia has been done since centuries ago. However, there are still many regions that do not already have proper documentation on this matter. This ethnobotany research aimed to analyze the forms of plant utilization and local wisdom in plant management by the indigenous people of Dusun Beleq, Gumantar Village, Kayangan District, North Lombok Regency. This research is a descriptive exploratory survey. Data collection was done by means of observation, interviews, documentation and literature study. Selection of informants was using purposive and snowball sampling methods. Qualitative and quantitative data were analyzed descriptively based on observations, interviews and ICS (Index of Cultural Significance) calculations.There were 10 kinds of plant utilization involving 86 species from 36 families. The plants were used as food, medicine, ritual plants, firewood, fodder plants, construction materials, handicrafts, aromatic plants, dyes and natural pesticides. Most of the plant species was used as food (41 species) with rice (Oryza sativa) as a plant with the highest ICS value among all plants in all categories (74 species). Local wisdom in term of natural resources utilization was reflected in community efforts in forest preservation, plants conservation, plants cultivation and harvesting. The novelty of this study is the revealment of local knowledge in plants utilization possessed by people in traditional village. This results of this study are expected to support the preservation of biological and cultural resources.